The level of environmental awareness among the kindergarten children according to some variables (A field study in Lattakia city) - SHraeba, Boshra; Traefe, Reem (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aimed to identify the environmental awareness among the kindergarten children (high, middle, low) in Lattakia city. In order to achieve this objective, the sample of the research of kindergarten children was selected from public and private kindergartens. The number of the sample reached (180) children of the age (5-6) years. This sample was chosen stratified randomly. The researcher used the descriptive method to achieve the objectives of the study. The research tool consisted of a non-verbal environmental awareness scale, which was developed by the researcher to suit the developmental characteristics of the kindergarten child in The Syrian Environment. The study found that the level of the environmental awareness of kindergarten children in Lattakia was high. The results also showed that there were no differences between kindergarten children in their environmental awareness according to gender and kindergarten's own.